Trypanotolerant livestock in West and Central Africa. Volume 1. General study - Trail, J.C.M.; Hoste, Christian H.; Wissocq, Y.J.; Lhoste, Philippe; Mason, I.L. (International Livestock Centre for Africa, 1979)
Review of the classification, geographic distribution, animal performance and productivity of trypanotolerant cattle, sheep and goats in 18 countries of west & central Africa, particularly N'dama cattle, West African Dwarf Shorthorn, and Zebu x N'Dama crossbreeds. Discussion on potential utilization and conservation of trypanotolerant livestock and recommendations for further research.